Кролик Питер и его друзья: сказки / Беатрис Поттер - Поттер Беатрис (Классика мировой литературы, 2010)
Экземпляры: М/а ДБ (20101209) / Инвентарный номер: 96786 / Цена: 151.20 / Авт.знак: П 64 / ГРНТИ: 17.82 / ББК: 84(4Вел)